The first and second law analyses of thermodynamic of pumpkin drying process - Akpinar, EK; Midilli, A; Bicer, Y (Elsevier Sci Ltd, 2006)
This paper is concerned with the thermodynamic analyses of single layer drying process of pumpkin slices via cyclone type dryer. Using the first law of thermodynamics, energy analysis was performed to estimate the ratios of energy utilization. However, exergy analysis was accomplished to determine the location, type, and magnitude of exergy losses during drying process by applying the second law of thermodynamics. It was concluded that the exergy losses went up with the increase of the energy utilization in both trays and drying chamber. The most exergy losses took place during the drying of pumpkin slices on the first tray. It is emphasized that pumpkin slices are sufficiently dried in the ranges between 60 and 80 degrees C and 20% and 10% of relative humidity at 1 and 1.5 in s(-1) of drying air velocity during 5.66-12 h despite the exergy losses of 0-1.165 kJ s(-1). (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: drying; thermodynamic analyses; energy and exergy; pumpkin